2005
DOI: 10.1097/01.ico.0000178740.14212.1a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Conjunctivochalasis on the Ocular Surface

Abstract: This study suggests that conjunctivochalasis has a great clinical impact on the ocular surface, and the newly developed operation is very effective in resolving patient complaints and also ocular surface damage in conjunctivochalasis with dry eye. It may also be suggested that the conjunctivochalasis has a negligible association with conjunctival inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 18 publications
(24 reference statements)
2
40
0
Order By: Relevance
“…Several research groups have previously reported evidence of a relationship between keratoconjunctivitis sicca and conjunctivochalasis [13,14,15,16]. Additionally, we also found that patients with idiopathic SCH had severe conjunctivochalasis-induced dry eye including SPK (data not shown).…”
Section: Discussionsupporting
confidence: 65%
“…Several research groups have previously reported evidence of a relationship between keratoconjunctivitis sicca and conjunctivochalasis [13,14,15,16]. Additionally, we also found that patients with idiopathic SCH had severe conjunctivochalasis-induced dry eye including SPK (data not shown).…”
Section: Discussionsupporting
confidence: 65%
“…13,[16][17][18][19] Bulbar conjunctival folds were first described by Hughes et al 21 and named conjunctivochalasis and they have been reported in severe dry eye patients. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] LIPCOF might represent the first mild stages of conjunctivochalasis and thus share the same aetiology. Several causes of bulbar conjunctival folds are hypothesised: conjunctival 'looseness' as a result of inflammatory processes, 23,27,36 a decrease of elastic fibres, 27,36 aging, 25,27 or lymphatic dilation by mechanical forces between the lower lid and conjunctiva that gradually interferes with lymphatic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Although initially asymptomatic, the consequence of CCh is dryness, tearing, subconjunctival hemorrhage, and incomplete lid closure. [2][3][4] The pro-inflammatory cytokines such as TNF-a and IL-1b are elevated in tears of CCh patients. [5][6][7] The coexisting ocular surface inflammation might further be aggravated by delayed tear clearance, which is frequently related to CCh.…”
mentioning
confidence: 99%